Unusual variant of esophageal atresia and tracheo-esophageal fistula: A case report - Rachael Stottlemyre; David M. Notrica; Mark McOmber; Erin Garvey (Elsevier, 2024)
Introduction: Esophageal atresia (EA) is the most common congenital anomaly affecting the esophagus. We describe an unusual variant of EA, which shares similarities with Type A but features a mid-esophageal segment attached to the trachea. Case presentation: A 38-week gestational age baby girl had prenatal diagnoses of EA and congenital cardiac anomalies. Postnatal attempts to advance an orogastric tube were unsuccessful, and EA was confirmed by chest X-ray showing the tube at the T2/T3 level without distal bowel air. Further workup included bronchoscopy, which identified a posterior tracheal outpouching without an apparent connection to the esophagus, and Cardiac CT, which revealed a mid-esophageal segment with a tracheo-esophageal fistula. Workup was consistent with complex esophageal anatomy with distinct proximal and distal pouches and a mid-esophageal segment attached to the trachea. A gastrostomy tube was placed for decompression and enteral feeds. Surgical intervention included closure and excision of the mid-esophageal fistula. The gap between the proximal and distal pouches was impressive, requiring cervical esophageal mobilization and two esophageal myotomies to add length, and concluded in a primary esophago-esophagostomy. Postoperative complications included a contained leak at the anastomosis, which was managed conservatively with placement of a feeding tube past the anastomotic site and resolved after 4 weeks. The patient required multiple esophageal dilations during the first two years of life and achieved successful closure of the gastrostomy at 25 months of age without further complications. Conclusion: Awareness of rare subtypes of EA enables surgeons to anticipate and address unique challenges that may arise during surgical intervention.